Efectos de promotores naturales y sintéticos sobre la brotación de tubérculos de papa (Solanum tuberosum) variedad super chola. - Medina Rubio, Marco Fabian (2011)
This research was aimed at determining the effects of natural and synthetic promoters on the sprouting of potato tubers (Solanum tuberosum) variety Super chola. Biol hormones were used at dilutions of 1:1, 1:5 and 1:10, and gibberellic acid in doses of 1.000 ppm, 1.500 ppm and 2.000 ppm. The research work was conducted in the canton Patate, parent parish, province of Tungurahua, in the liquor factory "The Blacksmith". Laboratory works were conducted under ambient temperature 16-210C, 40-50% relative humidity and 75% dark. The experimental design used was a D.B.C.A. with 7 treatments and 5 replicates, data collection was performed for 40 days, which was performed statistical analysis using Statistical Analysis System (SAS). ANOVA procedure was used for the analysis of variance and Tukey test (0,05). We conducted an economic analysis of costs of implementing each treatment. From the results it provides the best treatment is the application of 2.000 ppm gibberellic acid GA3, because it promotes sprouting of potato tubers (Solanum tuberosum) variety Super chola from 5,4 days. T3 treatment (2.000 ppm gibberellic acid GA3) was that with the increased cost effects of natural and synthetic promoters on the sprouting of potato tubers (Solanum tuberosum) variety Super chola at a cost of $ 7,41 and T7 treatment (Witness without promoter) had the lowest cost with a value of $ 4,63. To promote the sprouting of potato tubers (Solanum tuberosum) variety Super chola, apply 2.000 ppm gibberellic acid GA3.